1994
DOI: 10.2105/ajph.84.11.1768
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of hypertension awareness, treatment, and control in an insured population.

Abstract: OBJECTIVES. The purpose of the study was to identify the determinants of awareness, treatment, and control of hypertension in a population with full access to medical care. METHODS. Unionized New York City health care workers (n = 1394) with comprehensive medical insurance were screened for hypertension. Union records documenting all physician visits and prescription medications for the year before screening provided the opportunity to relate patterns of treatment to blood pressure outcomes. RESULTS. Of the 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
2
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 31 publications
(7 reference statements)
3
71
2
2
Order By: Relevance
“…Several studies reported that men achieved better control, others showed that female sex is a predictor of treatment success and some found no differences between the sexes. [34][35][36][37][38] In our study, no significant differences of BP control between men and women under treatment were found over time. However, 70% of our patients were women and this finding is consistent with a systematic review that showed that in developing countries, overall, women were more aware of their hypertension status and more likely to get pharmacological treatment.…”
Section: Discussioncontrasting
confidence: 59%
“…Several studies reported that men achieved better control, others showed that female sex is a predictor of treatment success and some found no differences between the sexes. [34][35][36][37][38] In our study, no significant differences of BP control between men and women under treatment were found over time. However, 70% of our patients were women and this finding is consistent with a systematic review that showed that in developing countries, overall, women were more aware of their hypertension status and more likely to get pharmacological treatment.…”
Section: Discussioncontrasting
confidence: 59%
“…This trend is consistent across socioeconomic status and across various age groups, and it has also shown to be true in a study from the U.S. when services were provided for no fee. 24 Alt described the pattern of preventative health care use among men in the U.S., showing that men have a lower number of ambulatory care visits, a longer interval between visits, and they are less likely than females to have a regular family physician. 25 Several other studies have attributed the poorer health status of males to a lack of primary health care use.…”
Section: Discussionmentioning
confidence: 99%
“…57 Others have documented low rates of BP control even in a fully insured group of unionized health workers with ample access to primary care providers. 58 Finally, other nonfinancial barriers to care exist in our population, including lack of transportation, exposure to violence, and living in a supervised setting. 44 Our findings show that in an indigent population, having a regular source of care, having recently been to a doctor, costs not being a deterrent in purchasing antihypertensive medications, having health insurance, and being compliant with antihypertensive medication regimens are significantly associated with controlled hypertension.…”
Section: Discussionmentioning
confidence: 99%